EFEKTIVITAS JAMUR BEAUVERIA BASSIANA DAN PUPUK ORGANIK CAIR KEONG MAS TERHADAP KERUSAKAN TANAMAN DAN HASIL TERUNG VARIETAS LAGUNA F1 - Erwin Arief Rochyat; Karno Karno; Candra Catur Nugroho; Kartika Dewi Ramadhani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
This research was aimed to determine the effect of Beauveria bassiana and golden snail  liquid organic fertilizer (LOF) and their interaction on plant damage and yield of eggplant of Laguna F1 variety. This research was arranged by Randomized Block Design (RBD) with 3 x 3 factorial analysis with three replications. 1st factor was the application of Beauveria bassiana (B) consisting of 3 levels, i.e. b0 (control or no treatment), b1 (20 g Beauveria bassiana L-1 water), and b2 (40 g Beauveria bassiana L-1 water). 2nd factor was the application of golden snail LOF (P) consisting of 3 levels, i.e. p0 (control or no treatment), p1 (21 ml LOF L-1 water), and p2 (42 ml LOF L-1 water). The results showed that the application of Beauveria bassiana and golden snail LOF and their interactions hadn’t significant effect on all parameters. The highest average yield per hectare (t ha-1) was obtained in treatment b2 (40 g Beauveria bassiana L-1 water) which was 13.62 t ha-1, p2 (42 ml LOF L-1 water) was 14.27 t ha-1, and the treatment combination b1p2 (20 g Beauveria bassiana L-1 water and 42 ml LOF L-1 water) was 15.07 t ha-1. Meanwhile, the lowest intensity of plant damage was obtained in treatment b2 (40 g Beauveria bassiana L-1 water) which was 13.33%, p2 (42 ml LOF L-1 water) was 15.56%, and treatment combination b1p2 (20 g Beauveria bassiana L-1 water and 42 ml LOF L-1 water) was 8.33%.